The Role of the Community Pharmacist in the Safe Use of Cibenzoline Succinate in the Elderly Patients - Nagano, Yuma; Oishi, Miya; Tsukioka, Ryota; Hasegawa, Yoshitaka; Fukaura-Nishizawa, Madoka; Maeda, Mamoru (The Journal of Community Pharmacy and Pharmaceutical Sciences, 2024)
Cibenzoline succinate is a renal-excretion type antiarrhythmic medication. There have been few reports on prescribing of cibenzoline succinate to elderly patients, whose renal function is expected to decline. Therefore, we estimated creatinine clearance based on body weight and serum creatinine levels by age group as reported in the “National Health and Nutrition Investigation in 2019” by the Ministry of Health, Labour and Welfare, and compared cibenzoline upper limit doses accordingly with optimal cibenzoline prescriptions in the processed receipt data of insurance pharmacies. We also investigated the occurrence of dose reduction over time in patients whose initial cibenzoline dose exceeded the upper limit. The study indicates that some patients over 75 years old may have exceeded the upper dose limit for age-related decline in Ccr. Patients who exceeded their initial cibenzoline dose were significantly more likely to experience subsequent dose reductions. As such, pharmacy pharmacists should check the renal function of patients and optimize cibenzoline doses accordingly.